A fuzzy multi-criteria decision making methodology based upon the interval Type-2 fuzzy sets for evaluating renewable energy alternatives in Turkey. Issue 5 (3rd September 2017) - Balin, Abit; Baraçli, Hayri
Abstract: Energy is substantial for social development and has an essential role for the survival and development of human as an environmental factor. Due to the serious increase ofthe world's primary energy price and rapid development of Turkey's economy, energy consumption of Turkey has become a major problem. For that purpose, opinions of the decision makers upon the relative importance of selection criteria are determined by using a fuzzy AHP procedure based upon type-2 fuzzy sets, and fuzzy multi-criteria decision-making based upon the interval type-2 TOPSIS method is used to rank the best renewable alternative energy. In this paper, a fuzzy multi criteria decision making (MCDM) methodology was proposed to determine the best renewable energy alternatives for Turkey, because type-2 fuzzy sets provide additional degrees of independence to represent the uncertainty and the fuzziness of real world applications. The results showed that wind was the best alternative for Turkey's energy investments, as being followed subsequently by solar, biomass, geothermal, hydraulic and hydrogen. The results were based upon the opinions of three energy planning experts who ranked the energy alternatives according to the ten criteria we have selected.